Migratory Movements and Mortality of Peregrine Falcons Banded in Greenland, 1972–97 - Mattox, William G.; Restani, Marco (ARCTIC, 2014)
In 1972 we initiated a long-term study of Peregrine Falcons Falco peregrinus in West Greenland to evaluate population status and describe general breeding ecology. The study area encompassed approximately 6050 km2, spanning the area from the edge of the inland ice cap westward to the coast. From 1972 to 1997, we banded 1896 peregrines (1771 nestlings, 125 adults). Encounters of banded peregrines (n = 114) outside the study area occurred at locations from Greenland to Uruguay. In contrast to the equal sex ratio recorded in broods at banding, the sex ratio of nestling encounters was significantly skewed toward females. The majority (54%) of encounters involved capture and release by other falcon researchers, particularly those operating banding stations along the Eastern Seaboard and in southern Texas. Peregrines from Greenland appeared to reach wintering areas by late October or early November. Although male peregrines wintered significantly farther south than females, there was no significant difference in the mean date of capture along the East Coast of the United States in the hatch year (mean = 9 October ± 2.5 days for males and 9 October ± 1 day for females). Spring migration appeared to commence in early April, with breeding birds back on the study area by late May or early June. Despite the extensive recent use of satellite telemetry, long-term banding continues to play an important role in studies of peregrine migration, natal dispersal, and survival. En 1972, nous avons entrepris l’étude à long terme des faucons pèlerins Falco peregrinus dans l’ouest du Groenland dans le but d’évaluer l’état de la population et de décrire l’écologie générale de la reproduction. L’aire visée par l’étude comptait environ 6 050 km2, s’étendant ainsi du bord de la calotte glaciaire de l’arrière-pays jusqu’à la côte ouest. Entre 1972 et 1997, nous avons bagué 1 896 faucons pèlerins (1 771 oisillons, 125 adultes). Des faucons pèlerins bagués (n = 114) ont été repérés à l’extérieur de l’aire visée par l’étude, dans des ...